Dermatome mapping: easy to do with formidable results: our experience - Basu, Shouptik; Kirtania, Dona (International Surgery Journal, 2018)
Background: Although the recurrence rates after Hernia Surgeries have declined, a new complication, the chronic post-operative pain has crept up. The existing methods of assessment of post-operative disability and surgical limitations are non-consistent and unreliable. Álvarez et al suggested a novel way of mapping the affected dermatomes after hernia surgery and incorporating factors like side, source, type, distribution and intensity of pain into a classification system called Dermatome mapping classification (DMC). The DMC is an easy to do office based evaluation that uses just the surgeon’s ballpoint pen, and a photograph for further reference. Methods: We observed 100 patients’ after Open Hernioplasty, conducted a Dermatome mapping and summarized our result. Results: Most of our patients had some pain and discomfort within the first week of the surgery that gradually declined. The DMC successfully predicted an iatrogenic denervation and also provided on the incidence of post-operative pain 8% in the 100 patients whom we evaluated. The Ilio-inguinal nerve was the most commonly affected nerve. Conclusions: The DMC is an objective record of the subjective assessment of the post-operative patient and it provides the surgeon with an insight on the result and efficacy of the surgery being performed. The technique is equally productive for evaluating Open and Laparoscopic Hernia repairs or planning and evaluating Neurectomies for chronic pain.